Fiscal policy in a Stock-Flow Consistent (SFC) model - Wynne Godley; Marc Lavoie (Levy Economics Institute of Bard College, 2007)
This paper deploys a simple stock-flow consistent (SFC) model in order to examine various contentions regarding fiscal and monetary policy. It follows from the model that if the fiscal stance is not set in the appropriate fashionthat is, at a well-defined level and growth ratethen full employment and low inflation will not be achieved in a sustainable way. We also show that fiscal policy on its own could achieve both full employment and a target rate of inflation. Finally, we arrive at two unconventional conclusions: first, that an economy (described within an SFC framework) with a real rate of interest net of taxes that exceeds the real growth rate will not generate explosive interest flows, even when the government is not targeting primary surpluses; and, second, that it cannot be assumed that a debtor country requires a trade surplus if interest payments on debt are not to explode.
Keywords: E12; E62; F41; 330; Stock-Flow Consistency; Fiscal Policy; Public Debt; New Consensus on Monetary Economics; Current Account Deficit; Finanzpolitik; Geldpolitik; Leistungsbilanz; Auslandsverschuldung; Haushaltsdefizit; Regelgebundene Politik; Theorie